INTEGRATION OF MEANINGFUL LEARNING THEORY IN EXPLORING GEOMETRIC REASONING BARRIERS THROUGH THINK ALOUD PROTOCOL ANALYSIS - Ila Maya Suprapti; M. Mahmudi Prasetiyo; Surya Sari Faradiba (JME (Journal of Mathematics Education), 2026)
This study was motivated by the urgency of low geometric reasoning skills among students in Indonesia and the failure of traditional evaluation methods to capture students' mental dynamics in real time. The main objective of this study was to analyze in depth the reasoning process of students in order to obtain a complete cognitive picture of the mechanisms of meaningful learning and the manifestation of relational-instrumental understanding in solving geometric problems. This study uses a qualitative approach with a descriptive-exploratory design on a single subject, a vocational high school student in Probolinggo City with the initials MK, who was selected through purposive sampling. Data collection was conducted through the Think Aloud Protocol (TAP), supported by retrospective interviews to ensure data triangulation. Data analysis techniques involved verbatim transcription, segmentation, and hierarchical coding procedures to form a cognitive map of the subject. The specific findings show that the subject did not operate dichotomously but rather demonstrated an adaptive hybrid mechanism between instrumental and relational understanding. A crucial moment was identified at 03:26, where the subject performed self-correction that triggered the assimilation (subsumption) of new information into the cognitive structure, which manifested as a pause or visual latency. Contextually, the discussion reveals that the subject used instrumental understanding as a cognitive efficiency strategy after the problem structure was solved relationally. In addition, verbalization in TAP functions as external scaffolding that strengthens students' metacognitive awareness in detecting calculation anomalies. This study concludes that mastery of geometry requires time for visual assimilation before symbolic manipulation is performed.